Schneider Enterprise : Safety Blouse / Dhia Nadhirah Azizu...[et al.] - Azizul, Dhia Nadhirah; Zaharin, Nasri; Abdullah @ Yassin, Ahmad Fakrusy Syakir; Mawari, Muhd. Zulhaizan; Zakaria, Muhd. Thaqif; Nawawi, Muhd. Ali imran (2018)
The purpose of the business entrepreneurship plan is as the first step as a module before starting a business. This business plan is very important to a new company like Schneider’s Enterprise because it may help us to maintain our business longer in the Malaysia market.